What drives individuals to access the internet mostly using a cell phone? - Seungyun Yook; Yumi Jung (International Telecommunications Society (ITS), 2012)
Mobile Internet users can access content, applications, and services using their cell phones. Recent PEW Internet research shows that more than half of U.S. cell phone owners have smartphones. Among them, some people have adopted a mobile phone and use it as a major Internet access medium; they may use other devices such as a desktop computer, notebook, netbook, or tablet PC, but those are not included in their Internet access medium repertoire. This paper examines who accesses the Internet mostly using a cell phone among the Internet users who access the Internet at least occasionally and what makes them regard their cell phone as a major Internet access medium. The results of this paper show that users who use their cell phones as their major Internet access medium are more likely to have a smartphones on which apps can be installed and used, not to have other portable PCs, to be young, to have less education, and to be nonwhite. The limitation of this paper was discussed.
Keywords: 330; cell-based Internet access; PC-based Internet access; wireless computing devices